Pengembangan Komik Online Berbasis Webtoon Untuk Meningkatkan Pemahaman Moderasi Beragama di SMA 17 Batam - Fauziah, Yunia; Zakir, Supratman; M, Iswantir; Salmiwati, Salmiwati (Faidatuna, 2024)
This article aims to produce a webtoon-based online comic that can increase students' understanding of religious moderation implemented at SMA 17 Batam. The type of research used is development research with the ADDIE design (Analysis, Design, Develop, Implement and Evaluate). The research instruments used in this research were validation sheets, teacher assessment sheets, student assessment sheets, and tests of students' understanding of religious moderation abilities. The techniques used were questionnaires, observations and interviews using descriptive and inferential analysis with the help of IBM SPSS Statistics 23. The results of the research show that the use of webtoon-based online comics can increase high school students' understanding of religious moderation. In this research, the author uses a development approach which includes several stages, such as preliminary study, planning, development and evaluation. The evaluation results show that webtoon-based online comics can increase the understanding of religious moderation of SMA 17 Batam students.